Unpredictable chronic mild stress exerts anxiogenic-like effects and activates neurons in the dorsal and caudal region and in the lateral wings of the dorsal raphe nucleus - Lopes, Danielle A.; Lemes, Jéssica A.; Melo-Thomas, Liana; Schor, Herbert; de Andrade, José S.; Machado, Carla M. [UNESP]; Horta-Júnior, José de Anchieta de Castro e [UNESP]; Céspedes, Isabel C.; Viana, Milena B. (Elsevier B. V., 2015)
In previous studies, we verified that exposure to unpredictable chronic mild stress (UCMS) facilitates avoidance responses in the elevated T-maze (ETM) and increased Fos-immunoreactivity in different brain structures involved in the regulation of anxiety, including the dorsal raphe (DR). Since, it has been shown that the DR is composed of distinct subpopulations of serotonergic and non-serotonergic neurons, the present study investigated the pattern of activation of these different subnuclei of the region in response to this stress protocol. Male Wistar rats were either unstressed or exposed to the UCMS procedure for two weeks and, subsequently, analyzed for Fos-immunoreactivity (Fos-ir) in serotonergic cells of the DR. To verify if the anxiogenic effects observed in the ETM could be generalized to other anxiety models, a group of animals was also tested in the light/dark transition test after UCMS exposure. Results showed that the UCMS procedure decreased the number of transitions and increased the number of stretched attend postures in the model, an anxiogenic effect. UCMS exposure also increased Fos-ir and the number of double-labeled neurons in the mid-rostral subdivision of the dorsal part of the DR and in the mid-caudal region of the lateral wings. In the caudal region of the DR there was a significant increase in the number of Fos-ir. No significant effects were found in the other DR subnuclei. These results corroborate the idea that neurons of specific subnuclei of the DR regulate anxiety responses and are differently activated by chronic stress exposure.
Keywords: Anxiety; Dorsal raphe; Fos immunoreactivity; Serotonin; Unpredictable chronic mild stress